2018
DOI: 10.1177/1071100718782489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postoperative Ketorolac Administration on Bone Healing in Ankle Fracture Surgery

Abstract: Level IV, case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 52 publications
(81 reference statements)
0
16
0
2
Order By: Relevance
“…[6][7][8]32 Additionally, data regarding the safety and efficacy of NSAID use in patients after orthopaedic surgery are limited, with the few available studies providing conflicting results. 3,19,25 A previous study demonstrated positive effects of cannabinoids on musculoskeletal biomechanical and biological properties during healing. Kogan et al, 14 using a rat femoral fracture model, showed that CBD administered independently resulted in significantly increased maximal force and work to failure of the fracture site compared with control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8]32 Additionally, data regarding the safety and efficacy of NSAID use in patients after orthopaedic surgery are limited, with the few available studies providing conflicting results. 3,19,25 A previous study demonstrated positive effects of cannabinoids on musculoskeletal biomechanical and biological properties during healing. Kogan et al, 14 using a rat femoral fracture model, showed that CBD administered independently resulted in significantly increased maximal force and work to failure of the fracture site compared with control.…”
Section: Discussionmentioning
confidence: 99%
“…6-8,32 Additionally, data regarding the safety and efficacy of NSAID use in patients after orthopaedic surgery are limited, with the few available studies providing conflicting results. 3,19,25…”
Section: Discussionmentioning
confidence: 99%
“…С другой стороны, серия наблюдательных исследований, проведенных в последнее время, показала отсутствие негативного влияния НПВП на консолидацию переломов ЛК и костей голени [22][23][24][25]. По результатам метаанализа 13 исследований (3 клинических и 10 экспериментальных), проведенного К. Duchman и соавт.…”
Section: факторunclassified
“…In particular, ketorolac, a first-generation NSAID, has been well documented for its safety with intravenous, intramuscular, and local infiltrations. 5,12,15,21,24 Indeed, ketorolac has been effectively combined with spinal block during hip and knee reconstruction. 1,11,13 However, a literature search has shown that there is limited information related to the use of local ketorolac injection for early postoperative analgesia in foot and ankle surgery.…”
Section: Introductionmentioning
confidence: 99%